Development of Andrographolide‑chitosan Solid Dispersion System: Physical Characterization, Solubility, and Dissolution Testing (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The purpose of this study was to determine the effect of various chitosan concentration on the psychochemical characteristic, the solubility, and dissolution of andrographolide-chitosan solid dispersion system. Materials and Methods: Andrographolide-chitosan solid dispersion system was prepared by solvent wetting-spray drying method in various drug to polymer ratio of 1:1, 1:2, 1:3, 1:4, and 1:5. The results were evaluated for morphology, physical state, drug content, solubility, and dissolution rate. Results and Discussion: The andrographolide-chitosan solid dispersion system particles showed spherical shapes analyzed by scanning electron microscopy. Infrared spectra of solid dispersion systems showed a similar absorption pattern as the drug compound. Differential thermal analysis and X-ray diffraction analysis showed a reduction in melting point and crystal intensity. The study revealed a 1.75 times increase in andrographolide-chitosan solid dispersion system solubility and 3.1 times for dissolution rate compared to andrographolide compound, respectively. Conclusion: An increase in chitosan amount in andrographolide-chitosan solid dispersion system resulted in decreasing crystallinity and a melting point of andrographolide, which had a positive effect on increasing solubility and dissolution rate.